An econometric analysis of the impact of structural changes on the aggregate output of the United States - Germinal G. Van (Economics and Econometrics Research Institute (EERI), 2021)
Structural changes play an essential role in the economic development of a country. They represent the evolution of economic dynamics within the macroeconomy. As we know, the economic sectors of a country do not affect the whole economy equally and their level of output generates economic fluctuations. The purpose of this paper is to analyze the impact of the three major economic sectors on the aggregate production of the United States since the 1990s. This paper essentially argues that the service sector is the sector that has contributed the most to the development of the U.S. economy since the 2000s because technological progress increased the rapid changes in the structure of the macroeconomy. Through the use of several econometric methods, we aim to rigorously analyze how the economic policy of each sector impacted economic growth.
Keywords: C33; C49; E22; N27; O43; 330; Econometrics; Economic Policy; Statistical Methods; Macroeconomics; Structural Changes; Quantitative Methods